Porous palladium aminophosphates: synthesis, characterization, antimicrobial and cytotoxicity studies1. Issue 82 (5th September 2015) - Rajini, Anumula; Adepu, Ajay Kumar; Chirra, Suman; Venkatathri, Narayanan
<x xml:space="preserve">Abstract</x> Novel palladium aminophosphates have been synthesized at room temperature in solvent free condition. They are characterized in detail. Their antimicrobial and cytotoxicity studies were carried out.